2021
DOI: 10.1097/brs.0000000000003943
|View full text |Cite
|
Sign up to set email alerts
|

Functional Ability Classification Based on Moderate and Severe Kinesophobia and Demoralization Scores in Degenerative Spine Patients

Abstract: Study Design. A prospective cohort study. Objective. To assess the relationship of fear avoidance and demoralization on gait and balance and determine a threshold score for the Tampa Scale for Kinesophobia (TSK) and the Demoralization Scale (DS) that identifies spine patients with gait and balance dysfunction amplified by underlying psychological factors. Summary of Background Data. Fear avoidance and demoralization are crucial components of mental health that impact the outcomes in spine surgery. However, int… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
1
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 17 publications
0
1
0
Order By: Relevance
“…A study with patients with degenerative spine conditions, found that higher scores on the Tampa Scale of Kinesiophobia (TSK) and the Demoralization Scale (DS), correlate with worse gait and balance 1 . This led the authors to conclude that “psychological factors … contribute to significantly worse function,” and that their study “does advance the clinical utility of TSK and DS … to help identify… patients… who may benefit from additional behavioral therapy before and after surgery.” 1 …”
mentioning
confidence: 99%
“…A study with patients with degenerative spine conditions, found that higher scores on the Tampa Scale of Kinesiophobia (TSK) and the Demoralization Scale (DS), correlate with worse gait and balance 1 . This led the authors to conclude that “psychological factors … contribute to significantly worse function,” and that their study “does advance the clinical utility of TSK and DS … to help identify… patients… who may benefit from additional behavioral therapy before and after surgery.” 1 …”
mentioning
confidence: 99%